Some things change, some things stay the same: a longitudinal analysis of cancer caregivers' unmet supportive care needs. Issue 7 (3rd September 2012) - Girgis, Afaf; Lambert, Sylvie D.; McElduff, Patrick; Bonevski, Billie; Lecathelinais, Christophe; Boyes, Allison; Stacey, Fiona
Abstract Objective The objective of this study was to identify caregivers' unmet needs and the psychosocial variables associated with unmet need count within the first 24 months post‐survivor diagnosis. Methods Caregivers completed a comprehensive survey measuring the primary outcome, psychosocial variables, and demographics of interest at 6 (n = 547), 12 (n = 519), and 24 (n = 443) months post‐survivor diagnosis. Results Although prevalence of unmet needs significantly decreased over time, almost a third of caregivers still reported unmet needs at 24 months. Unmet needs were more prevalent among caregivers of lung cancer survivors, at 6 and 24 months. Top ranking unmet needs across time included 'managing concerns about cancer coming back', 'reducing stress in the person with cancer's life', 'understanding the experience of the person with cancer', and 'accessible hospital parking'. At 24 months, some of the top ranking unmet needs were related to caregivers' well‐being and relationships. Increased interference in activities due to caregiving, anxiety, depression, avoidant and active coping, and out‐of‐pocket expenses was associated with reporting more unmet needs. Less involvement in caregiving roles and increased physical well‐being and social support were associated with reporting less unmet needs. For some variables (e.g. anxiety and depression), association with unmet needs strengthened over time. Conclusions This is the first longitudinal analysis of caregivers' unmet needs as they enter early and extended survivorship. Findings provide valuable insights into caregiver's unmet needs over time and identified a sub‐group of caregivers at risk of experiencing unmet needs, extending previous research and informing the timing and content of psychosocial services. Copyright © 2012 John Wiley & Sons, Ltd.